2021
DOI: 10.3390/antiox10121981
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Ameliorates Plant Metal Toxicity by Increasing Antioxidant Capacity and Reducing Pb and Cd Translocation

Abstract: Recently, nitric oxide (NO) has been reported to increase plant resistance to heavy metal stress. In this regard, an in vitro tissue culture experiment was conducted to evaluate the role of the NO donor sodium nitroprusside (SNP) in the alleviation of heavy metal toxicity in a bamboo species (Arundinaria pygmaea) under lead (Pb) and cadmium (Cd) toxicity. The treatment included 200 µmol of heavy metals (Pb and Cd) alone and in combination with 200 µM SNP: NO donor, 0.1% Hb, bovine hemoglobin (NO scavenger), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 84 publications
(118 reference statements)
2
8
0
Order By: Relevance
“…Plants activate a plethora of adaptive responses to withstand abiotic stresses, including a high accumulation of proteins [ 48 ]. The current study showed that the significant reduction in protein content due to Pb-induced damages is significantly mitigated by exogenous application of SNP, as shown in Figure 2 C. This result is in accordance with the previous reported result [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Plants activate a plethora of adaptive responses to withstand abiotic stresses, including a high accumulation of proteins [ 48 ]. The current study showed that the significant reduction in protein content due to Pb-induced damages is significantly mitigated by exogenous application of SNP, as shown in Figure 2 C. This result is in accordance with the previous reported result [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…SNP significantly ameliorated Pb-induced negative impacts on chlorophyll a and b contents, as shown in Figure 2 A,B. Similarly, under heavy-metal (Pb and Cd) stress, adding SNP increases chlorophyll and carotenoid concentrations in bamboo plants [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomass production can be improved through the application of Si in the form of soluble silicic acid Si(OH) 4 , which ultimately stimulates biochemical and molecular processes [67]. Shoot length and dry weight were observed to be increased by the addition of NO under Pb and Cd stress in Arundinaria pygmaea [12]. Similar findings were observed by Singh et al [68] in terms of an increase in root length, shoot length, and biomass under As stress in Oryza sativa plants.…”
Section: Discussionsupporting
confidence: 66%
“…Plant leaves were used for further analysis. The experiment included 16 treatments: (1) control, (2) As I (0.3 mM), (3) As II (0.5 mM), (4) As III (0.7 mM), (5) Si, (6) Si + As I, (7) Si + As II, (8) Si + As III, (9) NO, (10) NO + As I, (11) NO + As II, (12) NO + As III, (13) Si + NO, (14) Si + NO + As I, (15) Si + NO + As II and (16) Si + NO + As III.…”
Section: Plant Materials Growth Conditions and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation